PROSES PENGAJUAN NAMA UNTUK PERSEROAN TERBATAS - , DARU SUKENDRO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In order to know the author of the passage and understand the process of the establishment of PT , especially in the stages of the process of filing a name for the limited liability company , and also it can understand the people who read a bit of the process of the establishment of PT . For authors conducted Practice Field goal is to add to the experience , which the authors as a prospective professional must know the ins and outs of direct jobs that will be used by the writer in the face of the world of work . So in addition equipped theories during the course authors are also given the opportunity to directly apply the knowledge learned science . PT is a company which is by law declared as a company incorporated hukum.Dengan such status , the PT became the subject of laws supporting the rights and obligations , as a legal entity .